2011
DOI: 10.3168/jds.2011-4443
|View full text |Cite
|
Sign up to set email alerts
|

The dehorning of dairy calves: Practices and opinions of 639 farmers

Abstract: Calf dehorning is a routine husbandry practice on dairy farms that is justified by safety reasons for stockpersons and by a reduced risk of injures among herdmates. In Europe, the practice is regulated by law but little is known about the methods applied or about farmers' attitude to the practice. This study aimed to broaden the existing information on dehorning in dairy holdings by processing results of 639 farm questionnaires gathered in a traditional dairy area of northeastern Italy. Farm questionnaires wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
5
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 21 publications
9
69
5
10
Order By: Relevance
“…The 11-point Likert-scale for evaluating calf pain during disbudding without any pain medication was further divided into 3 classes to describe respondents' overall perceptions and to help make comparisons with other similar studies (Hoe and Ruegg, 2006;Gottardo et al, 2011): mild pain 0-3, moderate pain 4-7, and severe pain 8-10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 11-point Likert-scale for evaluating calf pain during disbudding without any pain medication was further divided into 3 classes to describe respondents' overall perceptions and to help make comparisons with other similar studies (Hoe and Ruegg, 2006;Gottardo et al, 2011): mild pain 0-3, moderate pain 4-7, and severe pain 8-10.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, producers reported that 10% of their disbudded calves received local anesthetics, 4% received a sedative, and 5% received analgesics before disbudding, and the majority of respondents were not willing to pay for veterinary services to treat disbudding-related pain (Gottardo et al, 2011). In Canada, use of sedatives or local anesthetics before disbudding was reported for 45% of herds, but apparently no analgesics were used (Vasseur et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Os métodos mais empregados para descorna são: a cauterização pelo calor e a cauterização química por meio da aplicação de pasta cáustica. A escolha do método depende em grande parte da experiência prévia e da preferência do operador (GRONDAHL-NIELSON et al, 1999;VICKERS et al, 2005;GOTTARDO et al, 2011;). Porém um estudo (COZZI, 2015) mostrou que a técnica mais utilizada dentre os países membros na União Européia é a descorna em bezerros utilizando o ferro quente, o que torna esta prática um dos principais fatores da ocorrência de queimaduras nesses animais.…”
Section: Introductionunclassified
“…Nas lesões de segundo grau a cicatrização ocorre em média entre 14 e 21 dias sem produção emprego de pasta cáustica (VICKERS et al, 2005;BROOM, 2008;STILWELL et al, 2009), a cauterização pelo calor utilizando ferro quente (GRAFF; SENN, 1999;GRONDAHL-NIELSON et al, 1999;FAULKNER;WEARY, 2000;VICKERS et al, 2005;DOHERTY et al, 2007;STILWELL et al, 2010;STILWELL et al, 2012;HENRICH et al, 2013;BATES et al, 2015;CARAY et al, 2015), a cauterização pelo frio -crio cirurgia (BENGTSSON et al, 1996) e a excisão do broto germinativo utilizando uma guilhotina ("scoop disbudding") (ESPINOZA et al, 2013;FRACCARO et al, 2013). Dentre todas estas técnicas a que mais se destacada por estar inserida no manejo rotineiro das propriedades leiteiras é cauterização pelo calor utilizando o ferro quente, tornando-se, portanto, um dos principais fatores da ocorrência de queimaduras em bezerros (GRONDAHL-NIELSON et al, 1999;GOTTARDO et al, 2011;VICKERS et al, 2005;COZZI et al, 2015).…”
Section: Introductionunclassified